On the frontier between 'high' and 'low' politics of migration in Burkina Faso - and the failure of emigration policies - Anne Sofie Westh Olsen (Danish Institute for International Studies (DIIS), 2014)
Migration policy research is biased towards receiving countries. Furthermore, even emigration policies are generally evaluated against their ability to control migration. This article asserts that 'filling the sending-country gap' should go beyond the role of policies in shaping (or reducing) migration. It should instead reflect the broader development goals of emigration policies, taking into consideration the capabilities of sending states. In this 'age of migration', it is striking how little we know about how policies can best be used by sending states as a tool for poverty alleviation, human capital development and labor market integration - even in the face of restrictive immigration policies on the other side of the border. One should also consider the aspirations of sending states in leveraging migration for development. With a case study on Burkina Faso - a mainly south-south sending country - policymaking is brought center stage in order to explore whether the current elaboration of an emigration policy signifies a change towards migration becoming - once again - 'high' politics in Burkina Faso.
Keywords: 300; Inequality and poverty; Migration and development; Migration and border management